Impact of Social Media Filter on Mental Health of Psychology Students of Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Beauty filters are widely used on social media platforms, and while they enhance appearance,they can also lead to negative psychological outcomes. Research has shown that exposure tounrealistic beauty standards can contribute to the development of body dissatisfaction, lowself-esteem, and negative body image. Furthermore, the use of beauty filters can perpetuatethe idea that physical attractiveness is the most important factor in social acceptance andsuccess, which can lead to feelings of inadequacy and anxiety. As a result, there is a need forfurther research to understand the potential long-term consequences of beauty filters onmental health and to develop strategies to minimize their negative effect.The majority of respondents aged eighteen to twenty (18-20) believed that social media filtershave a psychological impact. Individual variations affect these age groups the most, and theyare more attentive and aware of the impact of their surroundings, particularly social factors.Social media filters, in general, are growing increasingly popular because they enable users torepresent certain personalities and characters, generate creative content, and improve self-confidence.Nevertheless, using filters can create the illusion of digital beauty, in which users comparetheir looks to artificial standards, leading to a loss of confidence in real life. Users' expectationsof how they should appear may shift as they spend more time on social media. This viewimplies that individuals are typically satisfied with their looks, whether or not they utilize digitalfilters. Their total composite emotional impact average was four (4), suggesting that theperson is typically satisfied and confident in their looks, regardless of whether they utilizedigital filters.
Keywords: Mental Health